2020
DOI: 10.1186/s40816-020-00199-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of garlic extract in isoproterenol-induced myocardial infarction in a rat model: assessment of pro-apoptotic caspase-3 gene expression

Abstract: Background Myocardial Infarction (MI), also known as heart attack, is one of the most common cardiovascular diseases. Although certain drugs or mechanical means are used, day by day natural products such as herbs and spices based MI treatment is getting much popularity over the drugs or mechanical means for their pharmacological effects and have low or no side effects. This study was designed to assess the cardio-protective effect of methanolic extract of Bangladeshi multi clove garlic (Allium sativum) cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Lactate dehydrogenase and CK‐MB serve as a significant biomarker of myocardial infarction (MI). During the MI, the level of LDH and CK‐MB boosted as a result of the expansion of diseased condition 9,10 . The current study showed the elevated levels of LDH and CK‐MB in the ISO‐induced MI group rats, and the levels of LDH and CK‐MB were suppressed by BB treatment which considerably decreased myocardial necrosis.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Lactate dehydrogenase and CK‐MB serve as a significant biomarker of myocardial infarction (MI). During the MI, the level of LDH and CK‐MB boosted as a result of the expansion of diseased condition 9,10 . The current study showed the elevated levels of LDH and CK‐MB in the ISO‐induced MI group rats, and the levels of LDH and CK‐MB were suppressed by BB treatment which considerably decreased myocardial necrosis.…”
Section: Discussionsupporting
confidence: 48%
“…Exposure to ISO causes myocardial fibrosis in rats. Scar formation in myocardial tissue is often linked with the position and severity of ischaemia 9,10 . Previous research suggests that nitric oxide (NO) is a key molecule that significantly controls a variety of cardiac dysfunctions such as vasodilation, blood pressure, platelet and leucocyte adhesion and smooth muscle cell reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In isoproterenol induced myocardial ischemia activity of lecithin acyl transferase was substantially improved along with control of 3-hydroxy-3methylgutaryl-coA reductase enzyme by garlic element S-allyl cysteine sulfoxide [60]. According to scientists observations, cholesterol synthesis can be controlled up to 40-60% by SAC, S-propyl cysteine and S-ethyl cysteine [61].…”
Section: Cholesterol Lowering Potentialmentioning
confidence: 99%
“…The therapeutic potential of garlic (Allium sativum) has been demonstrated in the context of several pathological conditions (El-Saber Batiha et al, 2020;Nakamoto et al, 2020). Garlic has been reported to mitigate the neurotoxicity (Hassan et al, 2009), uropathogen invasion (Lionel et al, 2020), nephrotoxicity (Pedraza-Chaverri et al, 2008), and cardiac damage (Islam et al, 2020) associated with oxidative stress in animal models. The present study was designed to investigate the protective effect of garlic supplementation in rabbits that had been subject to nitrate poisoning.…”
Section: Introductionmentioning
confidence: 99%